Betri kennari fyrir vikið : viðbrögð við og lærdómur af krísustjórnun skólahalds í Reykhólahreppi vegna samkomubanns út af COVID-19 - Ágústa Ýr Sveinsdóttir 1989- (2020)
The following thesis is a final assignment for the Masters Program for Project Management at the Univeristy of Reykjavik. It is a case study that analysis the crises management at the times of COVID-19 in Reykhólahreppur, a rural community of 250 people, West Iceland. In this community as elsewhere in the country people have had to deal with natural disasters such as snow avalances, disastrous winds and lack of harvest. The corona virus in 2020 called for strict national rules concerning human relations. The government decided to put detailed rules for school activities in the hands of community leaders in each location. The theses looks into how Reykhólahreppur tackled the crises management, what the stakeholders in the local school found to work well and which mistakes were made. The theses tries therefore to bring together all lessons learned from the response to the COVID-19 epidemic. Perhaps the results can support still better responces to future crises.